Ação e racionalidade comunicativas em Habermas : problemas de mediação entre filosofia e pedagogia - Rossetto, Miguel da Silva (2007)
The goal, in this work, is to approximate the theory of action and communicative rationality in Habermas with the (re)formulation of a practical-theoretical meaning to the pedagogy. Specifically, we intend to investigate the possibility of passage from rationality understood through the modern paradigm of conscience to the moment when the rationality starts being understood through the communicative paradigm of inter subjectivity. With these purposes, we reconstruct Habermas argumentation emphasizing the relation language, rationality and action that, according to what we think, support the possibility of changing the educational paradigm. Therefore, from this reconstruction, the work is accomplished as it points indicatives of meaning construction to the comprehension of education as much in the scope of fundamentation as autonomous and rational science as in the field which concerns its effective dimension.